Early and Very Early Post-Transcatheter Aortic Valve Implantation Infective Endocarditis: Imaging Challenges - Nikoleta Hadjigeorgiou; Despo Melanarkiti; Theodora Eleni Plakomyti; Vasileios Demou; Vasileios Giannakopoulos; Chariton Sapouridis; Angeliki Mouzarou (Reviews in Cardiovascular Medicine, 2025)
Transcatheter aortic valve implantation (TAVI) is a minimally invasive procedure to treat severe aortic stenosis in select patients. Patients who have undergone TAVI are at high risk of infective endocarditis (IE), especially during the first year post-operation. Early diagnosis of IE is essential to initiate targeted antibiotic therapy and/or surgical intervention. However, the early detection of IE following TAVI poses significant diagnostic challenges. Current imaging techniques, including echocardiography, nuclear imaging, and magnetic resonance imaging, have varying degrees of sensitivity and specificity, each with inherent limitations. Nuclear imaging modalities, such as positron emission tomography/computed tomography using 18F-fluorodeoxyglucose (18F-FDG PET/CT) and white blood cell single photon emission computed tomography/computed tomography (WBC SPECT/CT), have shown promise in early IE detection, particularly due to the ability of these methods to identify metabolic and anatomical abnormalities. However, false-positive results related to post-operative inflammation complicate data interpretation, and limited data exist for using these methods in very early IE detection post-TAVI. Intracardiac echocardiography (ICE) offers enhanced visualization of prosthetic valve leaflets, but the invasive nature of ICE restricts its widespread use. Whole-body imaging, such as 18F-FDG PET/CT, facilitates the identification of distant lesions and systemic complications, aiding diagnosis and treatment decisions. Diagnosing IE after TAVI is especially challenging within the first 60 days post-procedure, a critical period when imaging findings may be inconclusive due to false negatives or limited availability of advanced modalities. This review underscores the diagnostic complexity of very early and early (0–60 days) IE post-TAVI, emphasizing the need for a multimodal imaging approach to overcome the limitations of individual modalities. Nonetheless, early antimicrobial therapy should be considered even without definitive imaging findings, highlighting the importance of clinical vigilance in managing this challenging condition.